Migration and remittances. Eastern Europe and the Former Soviet Union - Mansoor, Ali; Quillin, Bryce (Washington, DC, 2006)
Migration in Eastern Europe and Central Asia is unique and significant: ECA accounts for one-third of all developing country emigration, and Russia is the second largest immigration country worldwide. Migrants’ remittances, as a portion of gross domestic product, are also large by world standards in many of the net emigration countries of the region. Economic motivations and expectations regarding improvements in the quality of life at home currently drive short-term, long-term, and circular migration flows within ECA and between ECA and Western Europe. This report traces the trends of international migration and remittances in the region since the transition and their determinants. The report also looks at international migration policy in the region and how current bilateral migration schemes can be improved.